Keterbatasan Lapangan Kerja Formal dan Meningkatnya Minat Masyarakat Menjadi Ojek Online - Ciek Julyati Hisyam; Rifany Tri Aprilia; Mesya ashilah; Lovina Hasianna Tampubolon; Aditya Sangga Buana Ritcher; Daniala Madikna Balhah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study examines the rising interest in becoming online motorcycle taxi (ojek online) drivers amid limited formal employment opportunities. Using a qualitative descriptive approach, five informants who previously worked in the formal sector were interviewed through semi-structured interviews. Data were analyzed using the Miles and Huberman interactive model.The findings show that the decision to become an ojek online driver is driven by structural barriers in the formal labor market, such as strict age requirements, intense competition, dominance of personal connections in recruitment, and layoffs (PHK). Based on Merton's Strain Theory, this phenomenon is an innovative adaptation: individuals pursue economic goals through non-formal means due to limited access to formal employment. Informant motives vary, from choosing to fill spare time to forced survival strategies after job loss.This study provides a sociological understanding that the gig economy functions as a safety valve for labor structurally excluded from the formal sector.